Damping-off, a new disease of opium poppy caused by Phythium dissotocum - H.K. CHAURASIA; K.K. JANARDHANAN, M. ALAM, A. SATTAR (Indian Phytopathology, 2002)
The incidence, symptoms and pathogenicity of damping off of Papaver somniferum caused by P. dissotocum, in Uttar Pradesh, India, are described. The disease was prevalent in the district of Barabanki (40-60%) and at experimental fields in Lucknow (>60%). The disease occurred on seedlings of 2- to 4-weeks-old which distinguished it from downy mildew caused by Peronospora arborescens which appeared on seedlings older than 4 weeks and had different symptoms. Affected seedlings turned yellow and the roots and collar regions decayed. The casual agent was isolated from diseased roots and identified as P. dissotocum.